National Opinion Survey of Crime and Justice, 1995 - Flanagan, Timothy J. ([Verlag nicht ermittelbar], 1997)
The purpose of this survey was to provide legislators, public officials, and Texas residents with a reliable source of information about citizens' opinions and attitudes concerning crime and criminal justice related-topics. The data collection consists of two distinctly different files, National Data (Part 2) and Texas Data (Part 1), which can be linked or used separately for analysis. The survey questions concern neighborhood atmosphere and presentation of crime in the media, worries regarding possible attacks--both robbery and physical attacks, confidence in and opinions of police and their effectiveness, problems dealing with courts, and attitudes regarding prisoners and prisons, drug laws and drug problems, and juvenile gangs. Other questions focused on attitudes concerning the death penalty, guns, and the availability of firearms. The National Data file contains additional information expanding on the respondent's sources of crime news and gang-related questions. Demographic information on respondents includes sex, age, race, income, education, and religion.